Physical and mechanical properties of bayas wood (oncospema horridum) / Nur Syazwanie Jamal - Jamal, Nur Syazwanie (Faculty of Applied Sciences, 2015)
A study was undertaken to evaluate the physical and mechanical properties of Bayas wood, as the material is being promoted as the alternative raw material for furniture utilization. According to BS373:1957 (Methods of testing small clear specimen of timber), the samples are taken at different portion along the height (top, middle and bottom portion) and different wood zone (outer, center, inner zone) across the diameter of the trunk. The pattern of wood density, moisture content and shrinkage of Bayas wood at different portion and temperature were studied. The static bending tests were conducted to estimate the strength of the wood. The results specify that the wood position and height of trunk give highly significant value and varied within the trunk and at each height level.